GAMBARAN TINGKAT PENGETAHUAN PENGGUNAAN ALAT KONTRASEPSI PADA WANITA USIA SUBUR DAN DUKUNGAN PETUGAS DI DESA BEBANDEM KABUPATEN KARANGASEM BALI TAHUN 2014 - Nurul Farahan (E-Jurnal Medika Udayana, 2016)
DESCRIPTION OF USER EQUIPMENT CONTRACEPTION IN FERTILE WOMEN ON CHARACTERISTICS, LEVEL OF KNOWLEDGE, AND SUPPORT OFFICER IN THE VILLAGE BEBANDEM 2014 Data from 2010 Population Census note an increase in the rate of population growth, as well as the Bali Province. However, these excalations have not been followed by the implementation effectiveness of the family planning program. Data at Puskesmas Bebandem, we found the number of fertile couple than most other villages in the district Bebandem, number of fertile couple is 1815. However, the percentage of family planning acceptors in the Bebandem village at least than other villages in the districts Bebandem (54.98%). There are the kinds of factors that influence the decision of couples of childbearing age using contraception or not. From initial survey, we found characteristic, level of knowledge and health provider support had a diverse answer. However, from the aspect of attitude, affordability, support from husband and family had considered same enough. This study is a descriptive survey and using cross-sectional approach. Study sample are women of fertile couples in Bebandem village. The sample size used was 90, sampling techniques by convenience sampling (non-probability sampling). The variables studied were the involvement of predisposing factors (contraception, age, education level, parity, employment status, income level, level of knowledge), reinforcing factors (health provider support) and contraception usage. The collection of data done by interviews with the questionnaire. Data analysis performed were univariate and bivariate. From the research, more than half (55.6%) samples using contraception, while the rest (44.4%) did not use contraception. Older aged women with childs tends to not using contraception. Higher educational level, income, knowledge and health provider support tends to increase the usage of contraception.